2012
DOI: 10.1002/hrm.21485
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance work system implementation in small and medium enterprises: A knowledge‐creation perspective

Abstract: While it is well established that high‐performance work systems (HPWSs) affect firm‐level outcomes within large, complex organizations, less is known about how they create benefits for firms within the small‐business sector. Using a knowledge‐creation perspective, this study examines the impact of HPWSs in small and medium enterprises and examines whether the impact observed depends on the small‐business leader's capacity to obtain additional HR knowledge from an external expert, as well as the leader's HR bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 66 publications
1
42
0
1
Order By: Relevance
“…an increase in HR outcomes, there will be increase in organizational performance. (Katou & Budhwar, 2010;Klaas et al, 2012).…”
Section: Discussion/ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…an increase in HR outcomes, there will be increase in organizational performance. (Katou & Budhwar, 2010;Klaas et al, 2012).…”
Section: Discussion/ Resultsmentioning
confidence: 99%
“…The development of practices associated with the management of middle managers over time is not clearly understood in the current literature (Klaas et al, 2012;Heneman et al, 2000). In light of these observations this study examines how HRM practices affect organizational performance, in particular, which practices are likely to become dominant and formal early in small firms and the implications for survival and competitiveness of small growing firms.…”
Section: Hrm Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though profit oriented organization represented an important channel of disseminating HPWS through the involvement of supervisors and general managers whose majority have acquired the experience of human resource processes through previous managerial tasks or their relationship with other senior managers who has a greater knowledge of human resource processes (Klaas, Semadeni, Klimchak, & Ward, 2012). However, the responsibility of the human resource issues in the public organizations most times fall on the appointee of a political party in power or a registrar operating under his/ her dictate.…”
Section: Introductionmentioning
confidence: 99%
“…Again, Bryson (2001) found that, based on the evidence of the UK Workplace Employment Relations Survey, characteristics such as the size of the firm and the industry, and specific sets of managerial practices, had a stronger effect on managerial perceptions of the general organizational climate than organization-specific industrial relations realities. In a stream of HRM literature, adopting the managers' perspective instead of that of the employees to determine HRM outcomes has also been considered as appropriate (Wright et al 2001;Björkman et al 2007;Klaas et al 2012). As Wright et al (2001, p. 113) argue, the firm's managers "are in the ideal position to make decisions regarding how to balance the desires of and returns to shareholders, customers, and employees".…”
Section: Employee Effectiveness (Perf2)mentioning
confidence: 99%